Bentuk Profeminisme dalam Novel Perempuan yang Menangis kepada Bulan Hitam Karya Dian Purnomo - Nurazizah, Nurazizah (Aksara: Jurnal Bahasa dan Sastra, 2024)
The form of feminism raised by popular novels with the aim of describing how pro-feminism occurs is the background to this research. The data source for this research uses the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo and the data used is the form of pro-feminism that occurs in the novel as well as the form of feminism experienced by the main character. The method used is a qualitative descriptive method which is analyzed using content analysis techniques for the novel. The results of this analysis produced eight forms of pro-feminism data, the first form of pro-feminism from the character Dangu Toda was found in two data on pages 20 and 79. Second, the form of pro-feminism in Teman Magi was found in one data on page 119. The three, forms of pro-feminism in Tara were found in one data on page 105 Finally, the form of pro-feminism from the LSM, Gema Perempuan, found four data on pages 106, 122, 131, and 152. The form of feminism that occurs in this main character has four forms of gender concepts, namely gender and stereotypes, gender and marginalization, gender and subordination, and gender and violence. Keywords: feminism, novels, profeminism